Understanding JET-C quiescent phases with edge harmonic magnetohydrodynamic activity and comparison with behaviour under ITER-like wall conditioning. (1st April 2022) - Brunetti, D; Ham, C J; Graves, J P; Lazzaro, E; Nowak, S; Mariani, A; Wahlberg, C; Cooper, W A; Solano, E R; Saarelma, S; Frassinetti, L; Fontana, M; et al.
Abstract: An analysis of edge localised mode-free (quiescent) H-mode discharges exhibiting edge harmonic magnetoydrodynamic activity in the JET-carbon wall machine is presented. It is observed that the otherwise quiescent pulses with multiple- n harmonic oscillations are sustained until a threshold in pedestal electron density and collisionality is crossed. The macroscopic pedestal parameters associated with the quiescent phase are compared with those of a database of JET-ELMy discharges with both carbon and ITER-like wall (ILW). This comparison provides the identification of the existence regions in the relevant pedestal and global plasma parameters for edge harmonic oscillations (EHOs) in JET plasmas. Although the ELMy database scans pedestal collisionality and β values typical of ET-carbon quiescent operation, shaping and current are not simultaneously compatible with EHO existence. Nevertheless, ILW operation with JET-carbon quiescent-like parameters could in principle be achieved, and improved pedestal performance could be observed in more recent JET-ILW pulses.